2020
DOI: 10.36348/sjef.2020.v04i07.003
|View full text |Cite
|
Sign up to set email alerts
|

Policy Supports for Financial Stability

Abstract: The global financial crisis of 2008 has exposed numerous shortcomings in the traditional safeguards for financial stability in terms of different economic policies adopted so far. A system level perspective focusing on systemic risks with suitable policies and instruments was the felt need to combat vulnerabilities at their origin before spreading. The present study has analyzed the various policy options, indicators of systemic vulnerabilities, choice of tools and instruments for the regulatory and supervisor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…suggested that fostering youth involvement in agriculture is a worthwhile investment. Although, the participation of youths in agriculture is fundamental for economic development and poverty reduction World Bank, (2008), the factors influencing the willingness of youths to participate in agricultural activities include access to land, savings, and credit (Anyanwaokoro and Ogbu, 2017).…”
Section: Introduction 11 Background Of the Studymentioning
confidence: 99%
“…suggested that fostering youth involvement in agriculture is a worthwhile investment. Although, the participation of youths in agriculture is fundamental for economic development and poverty reduction World Bank, (2008), the factors influencing the willingness of youths to participate in agricultural activities include access to land, savings, and credit (Anyanwaokoro and Ogbu, 2017).…”
Section: Introduction 11 Background Of the Studymentioning
confidence: 99%